2019
DOI: 10.1523/eneuro.0003-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

PIM-Related Kinases Selectively Regulate Olfactory Sensations inCaenorhabditis elegans

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The C. elegans strains were grown and maintained at 20 °C on NGM (nematode growth medium) agar plates seeded with the E. coli strain OP50 or its streptomycin-resistant derivative OP50-1 using standard culturing methods [ 57 , 58 ]. Before experimentation, the C. elegans populations were synchronized by bleaching.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C. elegans strains were grown and maintained at 20 °C on NGM (nematode growth medium) agar plates seeded with the E. coli strain OP50 or its streptomycin-resistant derivative OP50-1 using standard culturing methods [ 57 , 58 ]. Before experimentation, the C. elegans populations were synchronized by bleaching.…”
Section: Methodsmentioning
confidence: 99%
“…To determine whether volatile compounds were attractive or aversive to the C. elegans nematodes, chemotactic assays were performed as described previously [ 35 , 58 ]. Briefly, 50–100 well-fed and washed young adults were placed in the middle of an NMG agar plate without food bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have identified the CP alpha 1, alpha 2 and beta 2 subunits as novel substrates for the oncogenic PIM1 kinase. The three serine/threonine-specific PIM family kinases regulate cell growth, metabolism, and motility, and have also neuronal functions [23][24][25][26]. They have been implicated in both hematopoietic malignancies and solid cancers [23,27,28], and are therefore promising targets for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%